Employee Loyalty: Systematic Literature Review - Sibarani, Imelda Juliana; Ishartati, Ishartati; Maulivia, Vivia Surya; Fergyanto E. Gunawan (SEAN Institute, 2024)
Employee loyalty is a critical factor in the success of the service and manufacturing sectors, with profound effects on both customer satisfaction and profitability. It is crucial to perpetually enhance employee loyalty to significantly boost competitive edge especially by minimizing the detrimental effects of high employee turnover. This research provides a detailed review of the methods and variables discussed in 38 peer-reviewed articles on employee loyalty, spanning from 2017 to 2023. It highlights the shortcomings in current empirical research, suggesting new pathways for future studies and identifying cultural disparities. Through the quantitative analysis, organization, and graphical representation of bibliometric data, including publication frequency and citation counts, derived from a thorough examination of the literature on in-depth analysis. Our results contribute essential insights and guidance for both practitioners and scholars, aiming to navigate the primary achievements and hurdles in contemporary empirical investigations into employee loyalty.